Complete denitrification of nitrate and nitrite to N2 gas by samarium(ii) iodide. Issue 77 (27th August 2020) - Marks, Walker R.; Baumgardner, Douglas F.; Reinheimer, Eric W.; Gilbertson, John D.
Abstract : The reduction of nitrogen oxides (N x O y n − ) to dinitrogen gas in a single vessel by samarium(ii ) iodide is reported. Abstract : The reduction of nitrogen oxides (N x O y n − ) to dinitrogen gas by samarium(ii ) iodide is reported. The polyoxoanions nitrate (NO3 − ) and nitrite (NO2 − ), as well as nitrous oxide (N2 O) and nitric oxide (NO) were all shown to react with stoichiometric amounts of SmI2 in THF for the complete denitrification to N2 .